2011
DOI: 10.1007/s13595-011-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the growth and yield of Pinus radiata in Bolivia

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Several growth and yield simulators are driven by a model that predicts dominant height as a function of stand age and site index (e.g., Shater et al 2011;Guzmán et al 2012). Use of the dominant height model assumes that dominant height is not reduced in thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Several growth and yield simulators are driven by a model that predicts dominant height as a function of stand age and site index (e.g., Shater et al 2011;Guzmán et al 2012). Use of the dominant height model assumes that dominant height is not reduced in thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed-effects models are also inferior to mixed-effect models when the aim is to make inferences about the population. However, several studies have shown that a fixed-effects model results in a smaller root mean square error (RMSE) than using only the fixed part of a mixed-effects model (Temesgen, Monleon, & Hann, 2008;Garber, Temesgen, Monleon, & Hann, 2009;Pukkala et al, 2009;Shater, de-Miguel, Kraid, Pukkala, & Palahí, 2011;Groom, Hann, & Temesgen, 2012;Guzmán, Morales, Pukkala, & de-Miguel, 2012a, Guzmán, Pukkala, Palahí, & de-Miguel, 2012bHeiðarsson & Pukkala, 2012). De-Miguel, Guzmán, & Pukkala (2013) found that, in the absence of calibration data, mixed-effects models should be used with caution.…”
mentioning
confidence: 99%
“…When comparing the productivity of E. globulus and P. radiata (the most planted exotic species in the study area) in Bolivia, eucalypts seem to be less productive since MAIs up to 25 m 3 ha -1 yr -1 have been observed in the most productive pine stands. The optimal rotation lengths for maximum wood production would be 5-10 years longer for the pines (Guzmán et al, 2012) on the best sites. To our knowledge, this is the first study in The relationship between stand mean diameter and maximum basal areas predicted by the adjusted model are biologically more consistent than those obtained directly from the fitted model, the latter overestimating tree mortality and, therefore, underestimating maximum stand basal area.…”
Section: Discussionmentioning
confidence: 99%